Культурная эволюция в эпоху формирования раннегородской цивилизации (по материалам раскопок Алтын-депе) - Кирчо, JI. Б.
Kir?o, L. ?., Cultural Evolution during the Era of Early Urban Civilization Formation (according to Altyn-tepe Excavation Data)